Improving Financial Literacy through Financial Management Training for Housewives Community - Abdu Khalik; Mukhtar Hamzah; La Ode Amijaya Kamaluddin (PT. Global Research Collaboration, 2025)
A low level of financial literacy among housewives can lead to family economic instability. Many housewives do not understand the importance of financial recording, budgeting, saving strategies, and wise debt management. This service aims to improve the financial literacy of housewives in the Makassar Women's Community through participatory-based training and mentoring. The methods used include community needs identification, practice-based training, and post-training mentoring for three months. The evaluation results showed a significant improvement in several financial aspects. Before the training, only 25% of participants routinely recorded finances, while after the training it increased to 80%. The ability to prepare a household budget also increased from 30% to 85%. In addition, awareness of saving and simple investment increased from 40% to 75%, while consumptive debt use decreased with an increase in awareness of managing debt from 20% to 70%. Participation in financial discussion communities also increased from 15% to 65%, indicating a change in mindset in family financial management. With these positive results, it is expected that housewives can apply the skills they have learned in a sustainable manner and share their knowledge with other community members. Program sustainability through financial discussion groups is key to maintaining the impact of this training. Overall, this service proves that an approach based on applicative training and mentoring can significantly improve financial literacy